Colonial Vestiges in the Representation of the Other: a Challenge for a Decolonizing Communication - Muro Ampuero, Eduardo César Augusto (2020)
DOI: 10.26439/contratexto2020.n033.4788 The main objective of this article is to present the importance and relevance of the various means of representation in the construction of the image of the Other (more specifically, the colonized Other). It is also considered that this type of representation of otherness is accompanied by a certain theory of truth, which establishes hierarchies regarding who can belong to the group, what type of knowledge is valid, what forms of spirituality is accepted, among other differentiations between “We” and “Them”. In that sense, in this work we try to outline, on the one hand, how from a certain form of knowledge production a paradigm is produced where the representations of the indigenous occupy a subordinate place in the intersubjective relations of our societies (also materialized in the body of this Other). On the other hand, we mention some examples of these representational vestiges of the indigenous, still present in Peruvian society, above all, disseminated through the media. And finally, the first two points are reflected on within the framework of a decolonizing communication.